Roast figs, sugar snow : food to warm the soul - Henry, Diana (Aster, a division of Octopus Publishing Group, 2023)
"Diana Henry's classic cookbook, Roast Figs, Sugar Snow, is now revisited, revised, and refreshed nearly 20 years after its first publication, with a new foreword by Nigel Slater and seven new recipes. Full of comforting delights from cold-weather climates, it features recipes gathered from Diana's travels to Scandinavia, the French and Italian Alps, Scotland, Ireland, and New England. This is irresistible food you'll cook over and over again. Choose Alpine dishes of melted cheese; autumnal pies and substantial winter salads; pastries from Viennese coffee houses; festive snow biscuits and - closer to home - Diana's definitive recipe for warming Irish stew. Of course, there is also a recipe for Sugar-on-Snow as well"--Amazon.com.